2019
DOI: 10.3390/bios9020048
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Design Study for Power Reduction in Organic Optoelectronic Pulse Meter Sensor

Abstract: This paper demonstrated a new design structure for minimizing the power consumption of a pulse meter. Monolithic devices composed of a red (625 nm) organic light-emitting diode (OLED) and an organic photodiode (OPD) were fabricated on the same substrate. Two organic devices were designed differently. One had a circle-shaped OLED in the center of the device and was surrounded by the OPD, while the other had the opposite structure. The external quantum efficiency (EQE) of the OLED and the OPD were 7% and 37%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Table 2 summarizes the PPG signal characteristics of Device-1 and Device-2. The method for quantifying the PPG signal quality using the SNR measurement was previously described in [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 summarizes the PPG signal characteristics of Device-1 and Device-2. The method for quantifying the PPG signal quality using the SNR measurement was previously described in [17].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the PPG signal was transmitted via serial communication block (SCB) or Bluetooth low energy (BLE). The analog circuit employed in this work was previously described, see [17] for more details. Figure 7A presents the portable pulse meter prototype that was proposed for wireless monitoring of the PPG signal, and Figure 7B illustrates the dimensions of our novel tool for fixing the biosensor pulse meter and the PCB, including the driver circuit and wireless MCU together with aluminum shield for further protection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[199,200] The Hattori group recently developed and characterized PPG sensors based on a red-emitting OLED using the phosphorescent emitter Ir(piq) 3 (peak wavelength: 625 nm) and an OPD containing a bulk heterojunction of DBP:C 60 . [201][202][203] Through optimization of device geometry and OPD layer structure, detection with signal-to-noise ratio (SNR) of 54 dB was achieved at a low power consumption of 0.6 mW. [203] The authors also demonstrated a wireless device that required even Figure 6.…”
Section: Oleds As Wearable Sensors For Health Monitoringmentioning
confidence: 99%
“…[ 26,27 ] Still the major challenge is to balance the efficiency of these detectors with their respective sensitivity toward high‐performance color selective OPDs for, that is, biomedical monitoring and sensing applications with low power consumption. [ 28 ] Especial interest herein lies on image sensors of multiple stacked semitransparent OPDs as opposed to a typical color filter array on panchromatic photodiodes with which different wavelengths are detected spatially separated from each other. [ 29 ] This allows for an increase in the geometric fill factor of such sensors, ultimately increasing the maximum resolution of an OPD.…”
Section: Introductionmentioning
confidence: 99%